Self-generation of magnetic fields - Dolan, T.J. (Вопросы атомной науки и техники, 2000)
The stars generate self-magnetic fields on large spatial scales and long time scales, and laser-produced plasmas generate intense self-magnetic fields on very short spatial and time scales. Two questions are posed: (1) Could a self-magnetic field be generated in a laboratory plasma with intermediate spatial and time scales? (2) If a self-magnetic field were generated, would it evolve towards a minimum energy state? If the answers turned out to be affirmative, then self-magnetic fields could possibly have interesting applications.